The content of adiponectin, resistin in serum and their ratio in patients with chronic heart failure in overweight and obesity depending on severity of disease, body mass index, age, gender and myocardium contractile ability - P. P. Bidzilya (Zaporožskij Medicinskij Žurnal)
Recently more and more attention of researchers is paid to determining of adiponectin and resistin role in the development, progression and outcomes of chronic heart failure (CHF) with overweight and obesity, given the continuing increase in the incidence of both pathologies.